Risk of prostate cancer in patients with Parkinson’s disease - Góralczyk, Wanesa; Borowiecka, Monika; Mikos, Eryk; Kanon, Karol (Journal of Education, Health and Sport, 2021)
Introduction: In recent years, an association between Parkinson’s disease and cancer has been reported with many clinical and epidemiological studies, encouraging the investigation of a potential common pathogenic pathway connected with both diseases. However, association between neurogenesis, medical treatment of Parkinson’s disease and occurence of prostate cancer (PCA) is still being discussed. Brief description of the state of knowledge: There were carried out population-based case-control researches that checked the connection between Parkinson’s disease and the risk of prostate cancer in Western (Canada, USA, UK, Denmark, Sweden, Israel) and Asian (Taiwan) populations. Studies revealed that Parkinson’s disease had significant association with reduced risk of prostate cancer in most of studied populations (Western) and increased in Asian population. Conclusions: Most of researches proved that Parkinson’s disease was associated with reduction of risk of prostate cancer, which decreased with increasing duration of Parkinson’s disease. The relationship between those conditions in Asian population needs to be checked in the future.